2010
DOI: 10.1111/j.1524-4733.2010.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence, Discontinuation, and Switching of Biologic Therapies in Medicaid Enrollees with Rheumatoid Arthritis

Abstract: This study highlights the poor adherence to and premature discontinuation without concurrent switching of RA biologics that should raise concern for clinicians as well as payers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 20 publications
5
54
1
3
Order By: Relevance
“…Demographic (age and gender distribution) and clinical characteristics of the final matched study sample were found to be consistent with those reported by other studies of patients with RA that were conducted using retrospective database analysis. 2,4,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] However, in contrast to other studies where the majority of participants were white, the present study had a majority Hispanic population (53.7%). 31,32,36,37 This was expected, since Hispanics have been reported to account for a significant proportion (≈ 40%) of the Texas population.…”
Section: Medication Effectiveness With the Use Of Tumor Necrosis Factcontrasting
confidence: 42%
See 2 more Smart Citations
“…Demographic (age and gender distribution) and clinical characteristics of the final matched study sample were found to be consistent with those reported by other studies of patients with RA that were conducted using retrospective database analysis. 2,4,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] However, in contrast to other studies where the majority of participants were white, the present study had a majority Hispanic population (53.7%). 31,32,36,37 This was expected, since Hispanics have been reported to account for a significant proportion (≈ 40%) of the Texas population.…”
Section: Medication Effectiveness With the Use Of Tumor Necrosis Factcontrasting
confidence: 42%
“…Adherence seen in this study was lower than has been reported in previous adherence studies that also used administrative claims data (commercial or Medicaid). 2,30,31,36 This may be because of the high Hispanic population (53.7%) in the study sample. Being of an ethnic minority has been associated with poor medication adherence.…”
Section: Medication Effectiveness With the Use Of Tumor Necrosis Factmentioning
confidence: 91%
See 1 more Smart Citation
“…A taxa de não adesão à terapia biológica verificada neste estudo foi alta; um terço dos pacientes não aderiu ao tratamento no primeiro ano. Comparando-se os resultados de outros estudos que também utilizaram dados administrativos, as taxas de não adesão variaram entre 25% e 68% 6,11,12,13,23 . Contudo, avaliaram apenas pacientes portadores de artrite reumatoide.…”
Section: Discussionunclassified
“…Em uma revisão sistemática que incluiu estudos com pacientes em uso de biológicos anti-TNF para o tratamento da artrite reumatoide 24 , foi encontrada uma taxa semelhante de não adesão, ou seja, de um terço. O estudo de Li et al 11 foi o que encontrou maior taxa de não adesão em pacientes portadores de artrite reumatoide, sendo de 68% para o etanercepte. Os autores sugerem que o fato pode estar relacionado com a característica da população estudada, que era de baixo poder aquisitivo.…”
Section: Discussionunclassified